Macrophytes Cultivation for Phytoremediation of Wastewater - Mustafa H.M.; Hayder G. (Springer Nature, 2024)
There is growing interest in phytoremediation, a plant-based wastewater treatment technique that is both environmentally benign and cost-effective. Macrophytes such as water lettuce (Pistia stratiotes) and duckweed (Lemna minor) were investigated for their efficiency in wastewater treatment for a period of ten days. The untreated and treated samples were subjected to turbidity and chemical oxygen demand (COD) tests at a detention time of 24h. The findings from the investigations indicated up to 91.9% reduction efficiency for water lettuce-treated effluent, while duckweed-treated effluent achieved 87.2% (turbidity) and 46% (COD) reduction efficiency. Therefore, the overall findings demonstrated that the two plants can be effectively used in the remediation of domestic wastewater. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.